Assessment of clinico-radiological and biochemical markers of rickets: A hospital based prospective follow up study - Kumar, Sanjay; Jyoti, Abha; Chaurasiya, Tushar; Kumar, Rajesh; Khan, Nadeem Ashraf (Asian Journal of Medical Sciences, 2021)
Background: Rickets is a disorder of defective mineralization due to deficiency of calcium and vitamin D and is more prevalent amongst the developing nations. Rickets has been ranked amongst the five most prevalent diseases in children of developing countries. The diagnosis of rickets is based on clinical features, biochemical studies and radiological signs and confirmed by response to treatment. Aims and Objectives: The purpose of this study is to evaluate the clinical, radiological and biochemical markers of the rickets by measuring the markers at the time of presentation, at 6 weekly intervals and after completion of treatment with standard regimen for rickets. Materials and Methods: 101 cases of nutritional rickets in age group 6 month to 18 years were allocated to receive combination therapy of calcium and vitamin-D according to their age and weight during a study period of 24 weeks. Radiographs (wrist and knee) and biochemical parameters (serum calcium, inorganic phosphate, alkaline phosphatase [ALP], and Vitamin-D), as well as clinical features, were evaluated at presentation, 6, 12, 18, and 24 weeks and response of treatment and markers were assessed at subsequent interval. clinical, radiological, biochemical parameters were evaluated statistically with Chi-square test for qualitative and 2 or more different variables by ANOVAs respectively. A P<0.05 was considered statistically significant analysis was done using Statistical Package for Social Sciences version 21.0. Results: At presentation, the mean dietary intake of calcium was low in all cases (6.11±0.78 mg/dl). Mean vitamin-D level was (23.05±8.14 ng/ml) indicative of vitamin-D deficiency. At the end of treatment (i.e., 24 weeks) clinical, radiological, and biochemical evidence of healing was observed. Normal serum ALP and complete radiological healing at 12 weeks was observed in 75% of subjects with the improvement of all markers. Conclusion: Children with rickets having low dietary calcium intake and low serum Vitamin-D levels have maximum number of markers at presentation. After intervention of combination regimen of calcium and Vitamin-D, remarkable improvement in clinical, radiological, and biochemical markers was found.